Circular relationship among ethic, social responsibility and reputation of cooperatives - Isabel Olmedo Cifuentes (AECOOP Escuela de Estudios Cooperativos, 2012)
Progressively, companies implement programs and activities based on business ethics, social responsibility and good governance. It is a justified strategy both in the current pressures from society, as the benefits that the firms obtain in terms of reputation and managing relationships with stakeholders. The proposal of this research is to apply the dynamics in the relationships of these variables to the case of cooperatives. In particular, it is studied the consequences of business ethics and social responsibility on the propensity to implement codes of conduct, and its impact on the achievement of good government in the cooperative and a greater reputation. Besides, it is argued that cooperatives with higher reputation are more likely to adopt principles based on ethics and social responsibility. In short, the main contribution of this paper is the justification for the circular relationship among these variables in the case of cooperatives, as they are organizations with an own singularity in terms of legal, economic and social.